High tumour mutational burden is associated with strong PD-L1 expression, HPV negativity, and worse survival in penile squamous cell carcinoma: an analysis of 165 cases - Hrudka, Jan; Hojný, Jan; Prouzová, Zuzana; Kendall Bártů, Michaela; Čapka, David; Zavillová, Nicolette; Matěj, Radoslav; Waldauf, Petr (Pathology, 2024)
Penile squamous cell carcinoma (pSCC) is a rare tumour with a variable prognosis. More prognostic markers linked to mutational signatures and the tumour immune microenvironment are needed. A cohort made up of 165 invasive pSCC was retrospectively analysed using formalin-fixed, paraffin-embedded tumour tissue, focusing on tumour mutational burden (TMB), programmed death ligand 1 (PD-L1) expression, microsatellite instability (MSI), the number of tumour infiltrating lymphocytes (TILs) expressing cytotoxic T-lymphocyte-associated protein 4 (CTLA4), HPV status determined by p16 immunohistochemistry, and several traditional histopathological variables. High TMB (>10 mut/Mb) was associated with high PD-L1 expression (TPS 50-100%), and HPV-negative status. High PD-L1 expression was linked to HPV negativity, a high number of intratumoural CTLA4+ cells, and brisk lymphocytic infiltrate. High TMB was a significant predictor of shorter overall survival (OS) in both univariate and multivariate analysis when using a median cut-off value of 4.3 mut/Mb, but not when using an arbitrary cut-off of 10 mut/Mb. Low CTLA4+ cell infiltration at the tumour invasion front was a marker of shorter OS and cancer-specific survival in both univariate and multivariate analysis. PD-L1 expression had no significant impact on prognosis. Only two cases were MSI high. The results support the hypothesis of two aetiological pathways in pSCC cancerogenesis: (1) SCC linked to HPV infection characterised by low TMB, less common PD-L1 expression, and a lower number of TILs; and (2) SCC linked to chronic inflammation leading to a high number of acquired mutations (high TMB), HPV negativity, increased neoantigen production (i.e., PD-L1), and high immune cell infiltration.
Keywords: CTLA-4 Antigen; Humans; PD-L1; tumour mutational burden; CTLA4; Penile Neoplasms; lidé; B7-H1 Antigen; nádory penisu; Penile squamous cell carcinoma; Papillomavirus Infections; Male; Retrospective Studies; Tumor Microenvironment; infekce papilomavirem; nádorové mikroprostředí; antigen CTLA-4; retrospektivní studie; spinocelulární karcinom; Carcinoma, Squamous Cell; antigeny CD274; mužské pohlaví